2001
DOI: 10.1111/1469-8986.3810041
|View full text |Cite
|
Sign up to set email alerts
|

Working memory constraints on syntactic processing: An electrophysiological investigation

Abstract: Event-related potentials (ERPs) and reaction times (RTs) were used to study how the processing of sentences with morphosyntactic violations is constrained by working memory (WM) capacity. The available WM capacity was varied by three orthogonal manipulations: (1) syntactic complexity; (2) additional WM load; and (3) verbal WM span. The processing of the morphosyntactic violations was reflected in longer RTs in ungrammatical compared with grammatical sentences, and in an anterior negativity and a centroparietal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
52
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(70 citation statements)
references
References 46 publications
18
52
0
Order By: Relevance
“…Furthermore, across agreement conditions, not all participants showed the same ERP effect -that is, a late positivity for short-distance agreement violations often did not correspond to a late positivity for long-distance agreement violations. While these between-subject differences in L1 ERPs differ from the dependency-driven latency modulations of Phillips et al (2005), they are consistent with the finding that ERPs for grammatical errors often have individual differences that are masked by grand averages (e. g. Kutas and Hillyard 1983;King and Kutas 1995;Vos et al 2001).…”
Section: |supporting
confidence: 83%
See 1 more Smart Citation
“…Furthermore, across agreement conditions, not all participants showed the same ERP effect -that is, a late positivity for short-distance agreement violations often did not correspond to a late positivity for long-distance agreement violations. While these between-subject differences in L1 ERPs differ from the dependency-driven latency modulations of Phillips et al (2005), they are consistent with the finding that ERPs for grammatical errors often have individual differences that are masked by grand averages (e. g. Kutas and Hillyard 1983;King and Kutas 1995;Vos et al 2001).…”
Section: |supporting
confidence: 83%
“…An ERP study in Dutch by Vos et al (2001) found that manipulations of WM load and between-subject differences in verbal WM span (as assessed by a listeningspan task) modulated the amplitude of the LAN in response to subject-verb agreement violations, with higher-span participants showing a larger amplitude LAN than lower-span participants; the same WM factors did not modulate the amplitude of the P600 in response to the same violations, but they did modulate its latency. Behavioral measures in the same study were not sensitive to WM manipulations, a discrepancy that highlights the utility of ERPs in this type of investigation.…”
Section: The Role Of Working Memory In L2 Processingmentioning
confidence: 99%
“…They also fit with the general Ôsubject-firstÕ strategy that has been shown for such patients in English, German, Italian, and Dutch, as well as for normal subjects working under perceptual or attentional loads (Strube, 1996;Vos, Gunter, Kolk, & Mulder, 2001a;Vos, Gunter, Schriefers, & Friederici, 2001b). The specific result for German object clefts is especially interesting in light of a current controversy on the nature and causes of receptive agrammatism (Friederici & Gorrell, 1998;Grodzinsky, 2000).…”
Section: Discussionsupporting
confidence: 64%
“…A lack of left-lateralization of anterior negativities, while rare, is not unprecedented. Bilateral (Hahne & Friederici, 2002;Münte & Heinze, 1994;Vos, Gunter, Kolk & Mulder, 2001) and right-lateralized (Osterhout & Nicol, 1999) anterior negativities for (morpho-) syntactic violations have been observed in other studies; however, no attempt has been made to systematically investigate experimental conditions which elicit bilateral and right-lateralized anterior negativities. The present study provides additional data that anterior negativities are not always left-lateralized; however, it is not possible to determine the factor that affects the distribution based on the present data.…”
Section: Grammaticality Effectsmentioning
confidence: 89%